كفايات بناء الاختبارات التحصيلية الجيدة لدى أساتذة التعليم الابتدائي - ضيف, حسين; الأسود, الزهرة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى التعرف على مستوى كفايات بناء الاختبارات التحصيلية الجيدة لدى أساتذة التعليم الابتدائي ومقارنتها بحد الاتقان والمحدد بــ75%، وبالاعتماد على المنهج الوصفي أجريت الدراسة على أساتذة التعليم الابتدائي بالمقاطعة التربوية رقم (5) بولاية الوادي، ولجمع بيانات الدراسة تم استخدام مقياس كفايات بناء الاختبارات التحصيلية (عدايكة،2019)، وتوصلت الدراسة إلى النتائج التالية: - مستوى كفايات بناء الاختبارات التحصيلية الجيدة لدى أساتذة التعليم الابتدائي منخفض ولم يصل إلى حدّ الاتقان والمحدّدة بــ75%. -لا توجد فروق ذات دلالة إحصائية بين أساتذة التعليم الابتدائي في كفايات بناء الاختبارات التحصيلية الجيدة تبعا لمتغير الجنس. - لا توجد فروق ذات دلالة إحصائية بين أساتذة التعليم الابتدائي في كفايات بناء الاختبارات التحصيلية الجيدة تبعا لمتغير الأقدمية في التدريس. الكلمات المفتاحية: كفايات بناء الاختبارات التحصيلية؛ الاختبار التحصيلي؛ أستاذ التعليم الابتدائي. Abstract: This study aims to identify the level of competencies of design good achievement tests for primary school teachers and compare them to the of perfection level defined as 75 ℅ depending on the descriptive comparative method, the study was conducted on primary school teachers in the educational district № 5 - province of the El Oued -, and to collect study data was used Measure of competencies of design achievement tests (Adaika 2019). The study reached the following results: -The level of competencies for design good achievement tests among primary school teachers is low and did not reach the level of perfection defined at 75%. -There are no statistically significant differences between primary school teachers in the competencies of design good achievement tests according to the sex variable. -There are no statistically significant differences between primary school teachers in the competencies of design good achievement tests according to the teaching experience variable.
مقال
Keywords: كفايات بناء الاختبارات التحصيلية ; الاختبار التحصيلي ; أستاذ التعليم الابتدائي; competencies of design achievement tests; achievement test; primary school teacher